2009
DOI: 10.1055/s-0029-1239532
|View full text |Cite
|
Sign up to set email alerts
|

Only Therapeutic ICOS:ICOSL Blockade Alleviates Acute Graft versus Host Disease

Abstract: Inducible co-stimulator (ICOS) interaction with its ligand (ICOSL) is involved in several T cell effector functions. While blockade of ICOS:ICOSL interaction in chronic graft versus host disease (GVHD) seems beneficial, results for acute GVHD remain controversial. To further elucidate its role in acute GVHD, C57BL/6 mice were reconstituted with allogeneic spleen cells in the absence or presence of ICOSL-blocking mAb. Mice reconstituted with allogeneic spleen cells experienced severe GVHD and died untreated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Our observations are consistent with previous reports that blockade of ICOS/ICOS-ligand interaction ameliorated acute and chronic GVHD 28 , 46 48 . On the other hand, our experiments have unraveled the role of ICOS/ICOS-ligand interaction in augmenting expansion of extrafollicular PSGL-1 lo CD4 + T cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our observations are consistent with previous reports that blockade of ICOS/ICOS-ligand interaction ameliorated acute and chronic GVHD 28 , 46 48 . On the other hand, our experiments have unraveled the role of ICOS/ICOS-ligand interaction in augmenting expansion of extrafollicular PSGL-1 lo CD4 + T cells.…”
Section: Discussionsupporting
confidence: 93%
“…This is the first example of efficacy of anti-ICOS mAb in treating chronic GVHD in a large outbred animal model. Earlier studies in mice suggested that ICOS:ICOSL blockade could alleviate GVHD [1517]. However, studies specifically addressing chronic GVHD were limited.…”
Section: Discussionmentioning
confidence: 99%
“…As the second signaling, ICOS/ICOSL costimulatory signaling is necessary for the homeostasis and function of various immune cell populations, and plays different roles in a series of disease models [24][25][26].…”
Section: Discussionmentioning
confidence: 99%